Salmonella Meningitis in the Newborns and Young Infants in Jakarta, Indonesia - Sumarmo Sumarmo; Muslim A. Nathin; Sofyan Ismael; W. A. F. J. Tumbelaka (Paediatrica Indonesiana, 1982)
Experience with salmonella meningitis in the newborn and young infantsbelow the age of 40 days hospitalized during the period 1976- 1979 was described. They constituted 8.6% of the 324 cases of purulent meningitis in children in approximately 20.000 admissions in the 4-year-period. There was a preponderance of males among the patients and the youngest case was 2 days old. The Salmonella serotypes isolated from cerebral spinal fluid were havana ( 17 cases J and oranienburg (11 cases). Of particular interest is the fact that 4 of the infants and their mothers showed the identical offending organisms isolated from the spinal fluid and rectal swab. The most common predisposing maternal obstetric complicationswere fever and premature rupture of the amniotic membranes, whereas the predisposing factors in the infants were infections, asphyxia arul prematurity. Ventriculitis, subdural effusion/empyema and hydrocephalus were the most common complications. A brief discussion has been made on the appropriate time to perform ventricular tap.